Deletions in the Epstein-Barr virus latent membrane protein-1 oncogene in Hodgkin's disease. Issue 4 (August 1995) - Santón, A; Manzanal, A I; Campo, E; Bellas, C
Abstract : Aims —To analyse the latent membrane protein-1 (LMP-1) gene in a series of patients with Epstein-Barr virus (EBV) positive LMP expressing ordinary and HIV associated Hodgkin's disease to detect possible genetic alterations and particularly the existence of deletions near the 3′ end of the gene. Methods —Expression of the EBV LMP-1 was assessed using immunohistochemistry in 186 cases of Hodgkin's disease and 31 cases of HIV associated Hodgkin's disease. Genomic DNA was extracted from frozen lymph node biopsy specimens from 25 cases of Hodgkin's disease and 11 of HIV associated Hodgkin's disease, all of whom expressed the LMP-1 protein within diagnostic Hodgkin and Reed-Sternberg (HRS) cells, and amplified by polymerase chain reaction (PCR) using primers specific for the different LMP-1 regions. Results —LMP-1 expression was observed in 106 of 186 Hodgkin's disease cases and in all 31 HIV associated Hodgkin's disease cases. Molecular analysis of the LMP-1 gene showed a high degree of genetic heterogeneity in the carboxy-terminal domain compared with the prototype B95-8 EBV strain, specially in the patients with HIV associated Hodgkin's disease. Variation in the size of the repeated region was found in 17 of 25 Hodgkin's disease and nine of 11 HIV associated Hodgkin's disease cases. Deletions of 30 base pairs near the 3′ end of the gene were detected in all cases of HIV associated Hodgkin's disease and in six Hodgkin's disease. In one case of Hodgkin's disease a larger deletion was observed. In all patients with LMP-1 deletion mutants, 50-90% of the diagnostic HRS cells expressed the LMP-1 protein. Conclusions —The presence of the 30 base pair deletion in all cases of HIV associated Hodgkin's disease supports previous studies that reported aggressive histological and clinical behaviour in tumours harbouring this deletion. This deletion may prolong the half-life of the protein which would explain the high levels of LMP-1 expressing HRS cells in those cases carrying LMP-1 deletions. That the 30 base pair deletion was present in all of the HIV associated Hodgkin's disease specimens suggests that impairment of immune function is a stringent requirement for the expansion of malignant cells infected by EBV strains containing the deleted LMP-1 gene.